2006
DOI: 10.1007/s00360-006-0095-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of body size on the diving behaviour and physiology of the bimodally respiring turtle, Elseya albagula

Abstract: In aquatic vertebrates that acquire oxygen aerially dive duration scales positively with body mass, i.e. larger animals can dive for longer periods, however in bimodally respiring animals the relationship between dive duration and body mass is unclear. In this study we investigated the relationships between body size, aquatic respiration, and dive duration in the bimodally respiring turtle, Elseya albagula. Under normoxic conditions, dive duration was found to be independent of body mass. The dive durations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
0
18
0
2
Order By: Relevance
“…This factor would further lower the threshold at which aquatic respiration becomes the more efficient mode for juvenile E. albagula . The results of a study by Mathie & Franklin (2006) further support the capacity for and importance of respiratory partitioning in juvenile E. albagula . Mathie and Franklin showed that in aquatic normoxia, juvenile E. albagula had a higher percent aquatic oxygen consumption than adults as a result of a larger mass‐specific cloacal bursae surface area.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This factor would further lower the threshold at which aquatic respiration becomes the more efficient mode for juvenile E. albagula . The results of a study by Mathie & Franklin (2006) further support the capacity for and importance of respiratory partitioning in juvenile E. albagula . Mathie and Franklin showed that in aquatic normoxia, juvenile E. albagula had a higher percent aquatic oxygen consumption than adults as a result of a larger mass‐specific cloacal bursae surface area.…”
Section: Discussionmentioning
confidence: 66%
“…This morphology resembles that of R. leukops , a species thought to demonstrate the greatest aquatic respiratory ability among aquatic chelonians (Legler & Georges 1993). Elseya albagula is believed to have a medium to high reliance on aquatic respiration, with aerobic dives of greater than 3 h recorded in the field and aquatic oxygen consumption percent in the laboratory ranging from 20–40% (adults) up to 100% (hatchlings) (Mathie & Franklin 2006; Gordos et al . 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Elseya albagula is considered a habitat specialist and co‐exists with two other locally endemic riverine specialist turtles ( Rheodytes leukops Legler & Cann, 1980, and Elusor macrurus Cann & Legler, 1994). Their requirement for well‐oxygenated, flowing waters seems closely associated with an interesting physiological adaptation allowing them to respire aquatically via highly vascularized cloacal bursae (Legler & Georges, ; Mathie & Franklin, ; Clark, Gordos & Franklin, ). Accordingly, these species are potentially highly sensitive to changes in habitat and flow regimes associated with river regulation and climate change (Thomson et al ., ; Hamann et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic respiration and diving behaviour in hatchling and juvenile turtles may be influenced by species morphology, physiology and behaviour. Owing to their small size, the mass‐specific surface area of hatchling and juvenile turtles is high, allowing them to extract a relatively larger amount of oxygen from the water compared with adult turtles (Mathie & Franklin, 2006). Reliance on aquatic respiration is therefore expected to be high in hatchling and juvenile turtles and this is likely to affect dive duration.…”
Section: Introductionmentioning
confidence: 99%